2020
DOI: 10.1038/s41380-020-0688-6
|View full text |Cite
|
Sign up to set email alerts
|

APOEε4 potentiates the relationship between amyloid-β and tau pathologies

Abstract: APOEε4 is the most well-established genetic risk factor for sporadic Alzheimer's disease and is associated with cerebral amyloid-β. However, the association between APOEε4 and tau pathology, the other major proteinopathy of Alzheimer's disease, has been controversial. Here, we sought to determine whether the relationship between APOEε4 and tau pathology is determined by local interactions with amyloid-β. We examined three independent samples of cognitively unimpaired, mild cognitive impairment and Alzheimer's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 63 publications
(78 reference statements)
4
42
1
Order By: Relevance
“…Several additional processes likely modulate A-tau interactions, including vascular changes (Box 3), ageing (Box 4), lipid metabolism, myelination, vesicle trafficking, autophagy, proteasome function, endosomal transport and mitochondrial function, since at least some experimental data are suggestive of both independent and interacting effects of A or tau on each of these processes. Indeed, lipid-metabolism related genes are related to the spread of both A and tau pathology in human AD 35 , and recent tau/A-PET revealed a synergistic interaction between APOE4 status and A levels on tau burden in the brain, as well as levels of p-tau in CSF, with the strongest effects seen in homozygous APOE4 carriers 110 . The LDL-receptor-related-protein 1 (LRP1) appears ideally positioned to modify A-tau synergy, since it can not only bind tau and mediate its neuronal uptake and spread, but also interact directly with APP, A and APOE4, thereby regulating A production and clearance 111,112 .…”
Section: Neuronal Activity Changesmentioning
confidence: 99%
“…Several additional processes likely modulate A-tau interactions, including vascular changes (Box 3), ageing (Box 4), lipid metabolism, myelination, vesicle trafficking, autophagy, proteasome function, endosomal transport and mitochondrial function, since at least some experimental data are suggestive of both independent and interacting effects of A or tau on each of these processes. Indeed, lipid-metabolism related genes are related to the spread of both A and tau pathology in human AD 35 , and recent tau/A-PET revealed a synergistic interaction between APOE4 status and A levels on tau burden in the brain, as well as levels of p-tau in CSF, with the strongest effects seen in homozygous APOE4 carriers 110 . The LDL-receptor-related-protein 1 (LRP1) appears ideally positioned to modify A-tau synergy, since it can not only bind tau and mediate its neuronal uptake and spread, but also interact directly with APP, A and APOE4, thereby regulating A production and clearance 111,112 .…”
Section: Neuronal Activity Changesmentioning
confidence: 99%
“…In humans, APOE4 carriers display a higher level of neurodegeneration for a similar level of amyloid pathology [11,63] and seem to progress faster to more advanced stages of the disease [67]. A PET-study in humans also demonstrated a combined effect of APOE status and amyloid load on tau pathology and spreading [61]. Importantly, recent work identified a protective APOE mutation in a human autosomal dominant AD setting.…”
Section: Discussionmentioning
confidence: 96%
“…A global neocortical [ 18 F]AZD4694 SUVR was estimated for each study participant by averaging the [ 18 F]AZD4694 SUVR from the precuneus, prefrontal, orbitofrontal, temporal, parietal, anterior, and posterior cingulate cortices. [ 18 F]MK6240 SUVRs were calculated in a Braak stage I–II region of interest (ROI) comprising the entorhinal cortex and hippocampus 16 , 17 as well as a temporal meta-ROI comprising the entorhinal cortex, hippocampus, fusiform, parahippocampal, inferior temporal, and middle temporal cortices. 18 …”
Section: Methodsmentioning
confidence: 99%
“…[ 18 F]MK6240 SUVRs were calculated in a Braak stage I-II ROI comprising the entorhinal cortex and hippocampus as reported in 16,17 , as well as a temporal meta-ROI comprising the entorhinal cortex, hippocampus, fusiform, parahippocampal, inferior temporal and middle temporal cortices 18 .…”
Section: Pet Image Acquisition and Processingmentioning
confidence: 99%